2022
DOI: 10.1177/09637214221102422
|View full text |Cite
|
Sign up to set email alerts
|

Sidelining Bias: A Situationist Approach to Reduce the Consequences of Bias in Real-World Contexts

Abstract: It has become common practice to conceptualize bias as an automatic response, cultivated through exposure to bias in society. From this perspective, combating bias requires reducing a proclivity for bias within individuals, as in many implicit-bias training efforts common in schools and corporations. We introduce an alternative approach that begins with the presumption that people are inherently complex, with multiple, often contradictory, selves and goals. When the person is conceptualized this way, it is pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Instead, it may be helpful to “sideline bias” (Okonofua, Harris, & Walton, 2022), that is, to reduce the hold that bias can have on men’s behavior by elevating positive aspects of men’s self-identity for which bias would be incompatible, such as an ideal professional self. Given the importance of social norms for men’s treatment of women (De Souza & Schmader, 2022), one may begin by establishing, conveying, and reinforcing community norms of inclusion and positive and mutually supportive interactions during goal pursuit (Murrar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it may be helpful to “sideline bias” (Okonofua, Harris, & Walton, 2022), that is, to reduce the hold that bias can have on men’s behavior by elevating positive aspects of men’s self-identity for which bias would be incompatible, such as an ideal professional self. Given the importance of social norms for men’s treatment of women (De Souza & Schmader, 2022), one may begin by establishing, conveying, and reinforcing community norms of inclusion and positive and mutually supportive interactions during goal pursuit (Murrar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At a higher level, much past research has identified ways to mitigate psychological barriers to retain women in STEM, typically by seeking to help women navigate settings in which they face risks of negative stereotypes and marginalization (e.g., Binning et al, 2020; Miyake et al, 2010; Walton et al, 2015). It is essential to complement such efforts by learning how to improve settings themselves (Walton et al, 2023; Walton & Yeager, 2020), such as to reduce the risk that people will be treated or received in biased ways (e.g., Murrar et al, 2020; Okonofua et al, 2016; Okonofua, Harris, & Walton, 2022; Walton et al, 2021). Toward this end, microinclusions align with and draw on the allyship literature (Brooks & Edwards, 2009; K.…”
Section: Microinclusions and Gender In Technology Settingsmentioning
confidence: 99%
“…Alternatively, future research should investigate whether it could be the case that beliefs other than those investigated here play a role in racial bias or that racial bias affects decision-making in classrooms. Additionally, it should be investigated whether interventions can mitigate disparities in school outcomes when individuals’ measured biases may not be the driving factor for disparities (Okonofua et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it should be investigated whether interventions can mitigate disparities in school outcomes when individuals' measured biases may not be the driving factor for disparities (Okonofua et al, 2022).…”
Section: Discussionmentioning
confidence: 99%